NEONATAL OUTCOME IN OBSTETRIC CHOLESTASIS PATIENTS AT AYUB TEACHING HOSPITAL ABBOTTABAD - Sultana, Ruqqia; Sarwar, Irum; Fawad, Ali; Noor, Shehla; Bashir, Rubina (Journal of Ayub Medical College Abbottabad, 2009)
Background: Obstetric cholestasis is a liver disease specific to pregnancy characterised by pruritus affecting the whole body but particularly the palms and soles and abnormal liver function tests. Objective of this cross sectional study was to evaluate obstetric cholestasis as a potential risk factor for adverse neonatal outcome. The study was conducted at Department of Obstetrics and Gynaecology, Unit ’˜B’, Ayub Teaching Hospital, Abbottabad from April 1, 2007 to March 31, 2008. Methods: All patients presenting with obstetric cholestasis irrespective of their age and parity were included in the study. Patients presenting with other causes of pruritus during pregnancy like Hepatitis (A, B, C), eczema, pruritus gravidarum and herpes gestationes were excluded from the study. Patients with liver involvement due to pre-eclampsia were also excluded. Baseline investigations, liver chemistries, viral screening, liver autoimmune screen, liver and obstetrical ultrasound were all done before the diagnosis was confirmed. Patients were treated symptomatically. Neonatal outcome was calculated in terms of increased incidence of passage of meconium, preterm delivery and foetal distress requiring delivery by Caesarean-Section. Results: Thirty patients were selected. Babies of 10 patients did well after delivery, 8 required NICU care within first 24 hours of birth and rest were delivered with low APGAR score. Two babies were delivered stillborn. Conclusion: Pruritus is quite common in pregnancy with obstetric cholestasis being one of them and earlier detection of the disease allows better identification of foetuses at risk. Keywords: Hepatic cholestasis, Pruritus, liver Function Tests, Foetal distress.